Una Aplicación Cotidiana de la Relatividad General - López-Domínguez, Julio César; Sabido, Miguel (Acta Universitaria, 2009)
In this article we present an everyday application of one of the fundamental theories ofnature, general relativity. We give a brief revision of how electrodynamics without any apparentapplication ends up beeing decisive in every day life. Finally we present how the effectsof general relativity are fundamental for accuracy of the global possitioning system (GPS).